2021
DOI: 10.1097/dss.0000000000002972
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Microneedling: A Comprehensive and Critical Review

Abstract: BACKGROUND Many studies have evaluated radiofrequency microneedling (RFMN) in various dermatologic conditions. However, the efficacy and safety of RFMN, and how it compares with other energy-based devices in a clinician's armamentarium, remains unclear. OBJECTIVE To review higher-quality evidence supporting RFMN and the dermatologic conditions which it can be used in. MATERIALS AND METHODS A search was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 46 publications
3
47
0
1
Order By: Relevance
“…[8][9][10] For acne scars, most of the patients show mild to moderate (25%-50%) improvement. [9][10][11] Fractional radiofrequency microneedling can be used in combination therapy with other lasers such as FNAL or FAL. Within acne scar subtypes, it is most effective in boxcar and rolling scars and least effective in icepick scars.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] For acne scars, most of the patients show mild to moderate (25%-50%) improvement. [9][10][11] Fractional radiofrequency microneedling can be used in combination therapy with other lasers such as FNAL or FAL. Within acne scar subtypes, it is most effective in boxcar and rolling scars and least effective in icepick scars.…”
Section: Discussionmentioning
confidence: 99%
“…One is RFMN, a system that uses microneedles. The benefits of RFMN include the delivery of uniform heat to dermal layers at controlled depth using microneedles with protection of the skin surface [ 18 20 ]. Our previous study found that the thermal response to RFMN treatment induced a wound healing cascade leading to long-term dermal remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of RFMN are slow and progressive, the procedure can be used repeatedly and safely in combination with other treatment modalities to augment its efficacy [ 20 ]. Recently, various wound healing accelerators, such as polynucleotides (PNs), stem cell culture media, and platelet-rich plasma, have received attention in wound and scar management.…”
Section: Discussionmentioning
confidence: 99%
“…12 Based on the quality of clinical studies, it is strongly recommended for acne scars and acne vulgaris, especially for patients with a darker skin phototypes. 12 Microneedling can also be combined with microdermabrasion, LED light, or other dermatological treatment systems with the goal of additive benefits, however, little research has been done on the efficacy of these combination treatments. 5,6 Microneedling devices should be sterilized with alcohol before and after every use as insufficient cleaning may increase the risk of infection or injury.…”
Section: T Ype S Of MI Croneedle Smentioning
confidence: 99%